Biodegradation of polylactic acid by a mesophilic bacteria Bacillus safensis. (March 2023) - Wang, Yujun; Hu, Ting; Zhang, Wanting; Lin, Jinwei; Wang, Zhanyong; Lyu, Shuxia; Tong, Haibin
Abstract: A mesophilic bacterial strain, Bacillus safensis PLA1006, was isolated from landfill soil and was tested for growth on polylactic acid (PLA) emulsion medium. The strain formed clear zones on the medium and produced protease and lipase. The macroscopic morphology of the PLA films was not changed significantly after treatment with Bacillus safensis PLA1006 but the films were whitened. Weight loss of PLA films was about 8% after 30 days of incubation with Bacillus safensis PLA1006 in mineral salt medium. Scanning electron microscopy revealed etching on the surface of PLA film treated by Bacillus safensis PLA1006. This also caused an increase in hydrophilicity of the PLA films surface. Attenuated total reflectance - Fourier transform infrared spectroscopy analysis of PLA films after treated by Bacillus safensis PLA1006 showed no new absorption peaks but a decrease in the intensity of all absorption peaks. The hydrolysis products of PLA by the strain contained monomers and oligomers of lactic acid. Zymogram detection showed that proteases may play a role in the degradation of PLA. Graphical abstract: Image 1 Highlights: ►A PLA degrading mesophilic bacteria Bacillus safensis PLA1006 were isolated. ►The weight loss of PLA films was about 8% after a 30-day incubation. ►Erosion and increase of hydrophilicity on strain-treated PLA film surface.